2021
DOI: 10.3389/fpsyg.2021.688376
|View full text |Cite
|
Sign up to set email alerts
|

Facial Expression Recognition and ReHo Analysis in Major Depressive Disorder

Abstract: Objective: To explore the characteristics of expression recognition and spontaneous activity of the resting state brain in major depressive disorder (MDD) patients to find the neural basis of expression recognition and emotional processing.Methods: In this study, two of the six facial expressions (happiness, sadness, anger, fear, aversion, and surprise) were presented in quick succession using a short expression recognition test. The differences in facial expression recognition between MDD patients and healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…The regional brain components of the salience network contain the dorsal ACC, putamen, anterior insula, and mid-cingulate, which mediate emotional regulation, monitoring for salient events, interoceptive awareness, and motivational behaviors (Yun and Kim, 2021). Consistent with previous studies (Yang et al, 2015;Fu et al, 2018;Liu et al, 2021), the ReHo values of the left putamen were reduced in patients with MDD. Previous studies have revealed that the left putamen volume was smaller in patients with MDD than that in HCs, and the left putamen was smaller in melancholic MDD compared with non-melancholic MDD (Sachs-Ericsson et al, 2018), suggesting that abnormal spontaneous neural activity in the left putamen of patients with MDD has an anatomical basis.…”
Section: Discussionsupporting
confidence: 80%
“…The regional brain components of the salience network contain the dorsal ACC, putamen, anterior insula, and mid-cingulate, which mediate emotional regulation, monitoring for salient events, interoceptive awareness, and motivational behaviors (Yun and Kim, 2021). Consistent with previous studies (Yang et al, 2015;Fu et al, 2018;Liu et al, 2021), the ReHo values of the left putamen were reduced in patients with MDD. Previous studies have revealed that the left putamen volume was smaller in patients with MDD than that in HCs, and the left putamen was smaller in melancholic MDD compared with non-melancholic MDD (Sachs-Ericsson et al, 2018), suggesting that abnormal spontaneous neural activity in the left putamen of patients with MDD has an anatomical basis.…”
Section: Discussionsupporting
confidence: 80%
“…6 Alterations in regional homogeneity have been shown in several psychiatric dis orders, including schizophrenia, bipolar disorder and major depressive disorder. [6][7][8] Functional abnormalities have been identified in the brain neural circuits of adolescents with borderline personality disorder. 2,9 For instance, abnormal activity has been shown in the limbic-cortical circuit and the default mode network (DMN), 3,4,10 both of which are crucial in emotion regulation 10,11 and in processing of a distorted self-image.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found differences in BOLD signals in the angular gyrus between patients with RDE or FDE and HCs, consistent with the present study ( Yuksel et al, 2018 ). Other studies have also reported that the ReHo and ALFF values in the left angular gyrus were lower in patients with MDD than in HCs ( Wang et al, 2012 ; Liu et al, 2021 ). Abnormalities in angular gyrus function can lead to cognitive impairment, a common clinical manifestation of MDD ( Lee et al, 2012 ).…”
Section: Discussionmentioning
confidence: 78%